2012
DOI: 10.1248/cpb.60.371
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Turbidimetric Screening for Heparin-Neutralizing Agents and Low-Molecular-Weight Heparin Mimetics

Abstract: Safer heparin-neutralizing agents are currently required to replace protamine, the use of which causes adverse effects such as anaphylaxia. Low-molecular-weight (LMW) heparin mimetics that potentiate antithrombin III (AT) action are also valuable as anti-thrombotics. This paper describes a high-throughput assay for both heparin-neutralizing agents and LMW heparin mimetics without the use of blood preparations. The assay is based on turbidimetric measurement of a solution of collagen, heparin, and a test compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…6 Previous approaches to screening heparin binders have used radioisotopes, affinity co-electrophoresis, 7 competitive inhibition assays 8 and recently, turbidimetric screening. 9 Having previously demonstrated that MalB could detect heparin in competitive conditions, we designed a simple dyedisplacement competition assay (Fig. 2) to probe synthetic heparin binders.…”
mentioning
confidence: 99%
“…6 Previous approaches to screening heparin binders have used radioisotopes, affinity co-electrophoresis, 7 competitive inhibition assays 8 and recently, turbidimetric screening. 9 Having previously demonstrated that MalB could detect heparin in competitive conditions, we designed a simple dyedisplacement competition assay (Fig. 2) to probe synthetic heparin binders.…”
mentioning
confidence: 99%
“…Our group has previously investigated inhibitors of collagen fibril formation using a high-throughput multi-well screening system that is based on monitoring turbidity increase as an indicator of collagen fibril formation. [12][13][14] In a chemical library containing 13 780 low-molecular-weight compounds, our screening identified only one hit compound, cisplatin, a well-known anti-cancer drug. We also clarified that the active compound was not cisplatin itself but rather a cisplatin derivative formed during storage in dimethyl sulfoxide (DMSO), a solvent commonly used in the preparation of chemical libraries.…”
Section: Introductionmentioning
confidence: 99%